Light‐Switchable Oxygen Vacancies in Ultrafine Bi5O7Br Nanotubes for Boosting Solar‐Driven Nitrogen Fixation in Pure Water - Wang, Shengyao; Hai, Xiao; Ding, Xing; Chang, Kun; Xiang, Yonggang; Meng, Xianguang; Yang, Zixin; Chen, Hao; Ye, Jinhua (Advanced materials (Weinheim), 2017)
Solar‐driven reduction of dinitrogen (N2) to ammonia (NH3) is severely hampered by the kinetically complex and energetically challenging multielectron reaction. Oxygen vacancies (OVs) with abundant localized electrons on the surface of bismuth oxybromide‐based semiconductors are demonstrated to have the ability to capture and activate N2, providing an alternative pathway to overcome such limitations. However, bismuth oxybromide materials are susceptible to photocorrosion, and the surface OVs are easily oxidized and therefore lose their activities. For realistic photocatalytic N2 fixation, fabricating and enhancing the stability of sustainable OVs on semiconductors is indispensable. This study shows the first synthesis of self‐assembled 5 nm diameter Bi5O7Br nanotubes with strong nanotube structure, suitable absorption edge, and many exposed surface sites, which are favorable for furnishing sufficient visible light‐induced OVs to realize excellent and stable photoreduction of atmospheric N2 into NH3 in pure water. The NH3 generation rate is as high as 1.38 mmol h−1 g−1, accompanied by an apparent quantum efficiency over 2.3% at 420 nm. The results presented herein provide new insights into rational design and engineering for the creation of highly active catalysts with light‐switchable OVs toward efficient, stable, and sustainable visible light N2 fixation in mild conditions. A facile wet chemical method for water‐assisted self‐assembly of 5 nm diameter Bi5O7Br nanotubes is reported. The obtained 5 nm Bi5O7Br‐NT is characterized with large surface area (>96 m2 g−1), suitable absorption edge, and sufficient surface oxygen vacancies of light switch. As a result, 5 nm Bi5O7Br‐NT delivers an excellent visible light driven photocatalytic N2 fixation performance with a NH3 generation rate of 1.38 mmol h−1 g−1 in pure water.